Morphometric features of local and foreign female pistachio cultivars and ecotypes in northeast Tunisian conditions - Chelli-Chaabouni A.; Ouni S.; Trad M.; Ouerghi I.; Ben Hamda H. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In the framework of the Tunisian pistachio research program, a number of orchards were created in different bio-climatic areas of the country. Local and foreign cultivars and ecotypes were planted to study their environmental adaptation, agronomic performance and nut quality. This study was performed in one of these orchards at the INRAT Unity of Agricultural Experimentations of Mornag. Local (7) and foreign (5) cultivars and ecotypes were installed since 1989 under rainfed conditions. Local accessions are ‘Mateur’, ‘Meknassy’, ‘Guermazi’, ‘El Guettar’, “6/6”, “8/7” and “28/4”, and foreign accessions are ‘Amiri’, ‘Jawad’, ‘Lassen’, ‘Ohadi’ and ‘Mumtaz’. Growth habit, vigor, yield and nut weight and size were evaluated during 2014. The growth habit of studied accessions was semi-erected or spreading. ‘El Guettar’, ‘Guermazi’, and the “8/7” ecotypes were the most vigorous whereas ‘Ohadi’ and ‘Amiri’ exhibited the lowest tree vigor. The fresh nut yield per tree varied between 0.43 and 23.4 kg. Foreign cultivars exhibited the lowest nut yields. It seems to be the consequence of their low adaptation. The “28/4” accession had the longest in-shell nut size while ‘Jawad’ nuts were the widest.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)